Frequency and clinical meaning of long-term degenerative changes after lumbar discectomy visualized on imaging tests - Mariconda, Massimo (Springer-Verlag, 2009)
The aim of this retrospective controlled study was to evaluate radiographic degeneration in the lumbar spine of patients who had undergone lumbar discectomy minimum 21 years earlier and its clinical meaning. Indeed, no previous investigation on degenerative changes occurring after lumbar discectomy with a comparable long follow-up has been published. The study participants consisted of 50 patients who had undergone discectomy for lumbar disc herniation. The mean length of follow-up was 25.3 ± 3.0 years. Patients were assessed by Short Form-36 Health Survey (SF-36), Oswestry Disability Index, and a study-specific questionnaire. Radiographic views of the lumbar spine were obtained from all patients and compared to those of 50 asymptomatic controls. A five-step published classification was used to assess the increasing severity of radiographic changes. CT or MRI scans were also available for 27 patients who had undergone discectomy. Moderate to severe radiographic changes were present in 45 patients (90%) and 34 controls (68%), respectively (P = 0.013). The most prevalent MRI/CT changes were loss of disc height (89%), facet joint arthritis (89%), and endplate changes (57%). Thirty-two of 33 subjects (97%) reporting pain during the last 12 months had significant degeneration on their radiographs, and the frequency of changes was higher with respect to subjects without pain (P = 0.040). In conclusion, standard lumbar discectomy frequently leads to long-term degenerative changes on imaging tests. The presence of moderate to severe degeneration is associated with self-reported pain.